Pemanfaatan Media Sosial Sebagai Sarana Edukasi Dalam Pencegahan Covid-19 - Purwanti, Santi; Jaja, Jaja; Rakhmayudhi, Rakhmayudhi; Adhi W., Satia; Fatia S., Sifah; Amelia R., Riska; Azzahra, Delia; Triana N., Lita (Journal Of Computer Science Contributions (JUCOSCO), 2022)
Subang is one of the regencies in West Java province which is still carrying out the handling and handling of Covid-19, especially the Pasirkareumbi village, as a form of community service, an educational program will be made for the community. One of the current problems is the lack of knowledge, especially the public about the Covid-19 virus and also related to vaccination, therefore it is necessary to do socialization, one way is using social media. The method used to educate is done in two ways, namely online and offline. Online is targeted at social media users by sharing posts in the form of information regarding the Covid-19 virus on social media such as WhatsApp and Instagram, while the Offline method uses banner media as well as socialization regarding the importance of Vaccination. From the results of this activity, the community will understand and know the importance of vaccination for body resistance and with full awareness to participate.